Constitutional Handcuffs - Richard Albert (Intergenerational Justice Review)
This article makes three contributions to the literature on constitutional change. First, it reinforces the theoretical foundations of constitutional entrenchment by defining the spectrum of constitutional permanence. Second, it offers an original taxonomy of entrenchment clauses, including preservative, transformational and reconciliatory entrenchment. Third, in concluding that absolute entrenchment undermines the participatory values that give constitutionalism its meaning, it proposes an alternative to entrenchment: the entrenchment simulator. Whereas entrenchment clauses prohibit constitutional amendment, the entrenchment simulator provides a promising alternative that both embraces the expressive function of entrenchment and remains consistent with the promise of constitutionalism.